Beauty of Distalization-case report - Prakash, Amit; Bharti, Chandni; Eapen, Jijo C; Upahayay, Saumya; Nayak, Bhagyashree (Orthodontic Journal of Nepal, 2023)
Maxillary molar distalization has been in used in orthodontics over a centennial. This approach has been used to attain space in the maxillary arch for relief of crowding, correction of Class II molar relationship and reduction of an increased overjet. This article reports the successful use of five molar distalization appliances, they are; the pendulum, distal jet, K- loop molar distalizer, double-loop Ni-Ti and the C- space regainer. All the five patients were in the age group of 12-20 years, who had Class II molar relationship with mild overjet and normal mandibular arch. In all the five patients maxillary molar distalization was efficient in correcting the borderline Class II malocclusion. Pendulum appliance was more efficient than others because it is easy to fabricate, cost-effective, less frequent activation and minimum anchorage loss. The practitioner requires a through understanding of the clinical indications of this procedure so that undue side effects can be minimized along with better incorporation in the orthodontic patient care.